Kaskitamasowin miýw-āyāwin - Van Bewer, Vanessa (Witness: The Canadian Journal of Critical Nursing Discourse, 2020)
The following is a poetic re-presentation of Madeline Dion Stout’s (2012) editorial: Ascribed Health and Wellness, Atikowisi Miýw-āyāwin, to Achieved Health and Wellness, Kaskitamasowin Miýw-āyāwin: Shifting the Paradigm.